Novel USH1G homozygous variant underlying USH2-like phenotype of Usher syndrome. Issue 2 (March 2021) - D'Esposito, Fabiana; Randazzo, Viviana; Cennamo, Gilda; Centore, Nicola; Maltese, Paolo Enrico; Malesci, Rita; D'Andrea, Luca; Bertelli, Matteo; Marciano, Elio; de Crecchio, Giuseppe; Pioppo, Antonino; Magli, Adriano; et al.
Purpose: Usher syndrome (USH) is an autosomal recessive disorder characterized by congenital sensorineural hearing impairment and retinitis pigmentosa. Classification distinguishes three clinical types of which type I (USH1) is the most severe, with vestibular dysfunction as an added feature. To date, 15 genes and 3 loci have been identified with the USH1G gene being an uncommon cause of USH. We describe an atypical USH1G -related phenotype caused by a novel homozygous missense variation in a patient with profound hearing impairment and relatively mild retinitis pigmentosa, but no vestibular dysfunction. Methods: A 26-year-old female patient with profound congenital sensorineural hearing loss, nyctalopia and retinitis pigmentosa was studied. Audiometric, vestibular and ophthalmologic examination was performed. A panel of 13 genes was tested by next-generation sequencing (NGS). Results: While the hearing loss was confirmed to be profound, the vestibular function resulted normal. Although typical retinitis pigmentosa was present, the age at onset was unusually late for USH1 syndrome. A novel homozygous missense variation (c.1187T>A, p.Leu396Gln) in the USH1G gene has been identified as causing the disease in our patient. Conclusions: Genetic and phenotypic heterogeneity are very common in both isolated and syndromic retinal dystrophies and sensorineural hearing loss. Our findings widen the spectrum of USH allelic disorders and strength the concept that variants in genes that are classically known as underlying one specific clinical USH subtype might result in unexpected phenotypes.